ATOMS: ALMA three-millimeter observations of massive star-forming regions – XII: Fragmentation and multiscale gas kinematics in protoclusters G12.42+0.50 and G19.88−0.53. Issue 2 (29th August 2022) - Saha, Anindya; Tej, Anandmayee; Liu, Hong-Li; Liu, Tie; Issac, Namitha; Lee, Chang Won; Garay, Guido; Goldsmith, Paul F; Juvela, Mika; Qin, Sheng-Li; Stutz, Amelia; Li, Shanghuo; et al.
ABSTRACT: We present new continuum and molecular line data from the ALMA Three-millimeter Observations of Massive Star-forming regions (ATOMS) survey for the two protoclusters, G12.42+0.50 and G19.88−0.53. The 3 mm continuum maps reveal seven cores in each of the two globally contracting protoclusters. These cores satisfy the radius–mass relation and the surface mass density criteria for high-mass star formation. Similar to their natal clumps, the virial analysis of the cores suggests that they are undergoing gravitational collapse (α _vir 2 ). The clump to core scale fragmentation is investigated and the derived core masses and separations are found to be consistent with thermal Jeans fragmentation. We detect large-scale filamentary structures with velocity gradients and multiple outflows in both regions. Dendrogram analysis of the H 13 CO + map identifies several branch and leaf structures with sizes ∼ 0.1 and 0.03 pc, respectively. The supersonic gas motion displayed by the branch structures is in agreement with the Larson power law indicating that the gas kinematics at this spatial scale is driven by turbulence. The transition to transonic/subsonic gas motion is seen to occur at spatial scales of ∼0.1 pc indicating the dissipation of turbulence. In agreement with this, the leaf structures reveal gas motions that deviate from the slope of Larson's law. From the large-scale converging filaments to the collapsing cores, the gas dynamics in G12.42+0.50 and G19.88−0.53 show scale-dependent dominance of turbulence and gravity and the combination of these two driving mechanisms needs to be invoked to explain massive star formation in the protoclusters.